Architecting Technological Resilience: Evaluating the Impact of Legacy System Modernization on Organizational Agility in the Age of Generative AI - Azzuan Azzuan; Zubaidi Budi Hartanto; Moh. Qomar Syarifuddin; Ahmad Faisol; Syafiq Amir (Yayasan Adra Karima Hubbi, 2026)
Background. Organizations are under immense pressure to modernize legacy systems to stay competitive in a fast-changing tech landscape. While Generative AI is recognized as a key driver for productivity and innovation, the specific link between upgrading old systems and achieving organizational agility in the AI era remains largely underexplored. Purpose. This study aims to evaluate how legacy system modernization impacts organizational agility within the context of Generative AI integration. It seeks to understand if these technical upgrades serve as a strategic foundation for fostering adaptability and long-term resilience. Method. The research utilized a mixed-methods approach, combining quantitative surveys and qualitative interviews. Data was gathered from key stakeholders across 30 organizations that have successfully completed the modernization of their legacy infrastructures. Results. The findings show significant improvements in decision-making speed, market responsiveness, and operational flexibility. The study highlights that modernization is a critical enabler for faster Generative AI adoption, which directly enhances an organization's overall agility. Conclusion. Modernizing legacy systems is a strategic investment rather than a mere technical necessity. It builds technological resilience and provides a vital framework for AI integration, offering organizations a pathway to sustained competitive advantage and better adaptability.